Structural model and reasoning in hierarchical diagnosis - Oleksiak, Jakub; Ligęza, Antoni (Computer Assisted Methods in Engineering and Science; Vol 12 No 2-3 (2005), 2022)
Fault diagnosis becomes more and more difficult and sophisticated task. This is so mainly due to growing complexity - contemporary technological systems are assembled from numerous components which cooperate and recursively include other components. The main goal of this paper consists in presentation of an approach which is able to reduce time of diagnosis and quantity of produced diagnoses by using hierarchical, logic-based approach. The reduction is achieved here due to two main factors . The first one is that a hierarchical model of systems is used. Such approach limits search space, because the system is considered at various levels of details and some diagnoses which are possible potential ones at more abstract levels can be verified to be impossible at more detailed levels. The second factor is that levels can be described with use of different kinds of a logic-based knowledge representation, what lets fit some best representation to a particular level.